A test of the Resource's and Bergmann's rules in a widely distributed small carnivore from southern South America, Conepatus chinga (Molina, 1782) (Carnivora: Mephitidae) - Schiaffini, Mauro Ignacio (2016)
Bergmann's rule is one of the most known biological rules and relates the body size variation to changes in latitude or temperature. Most recently, a "resource rule" had been presented, which explains several trends in body size, as a consequence of availability of resources. South American Conepatus chinga is one of the most widespread small carnivores in the Neotropics, being geographically distributed from Perú and Brazil to southern Argentina and Chile. This widely distributed species encounters a high environmental variability, which could affect body size and morphological variations. Here, I analyze geographical patterns of variation in body size and morphology estimated using a geometric morphometric approach from museum specimens. The associations between geographical patterns of variation in body size and morphometry and climatic and/or environmental variables were evaluated, using several databases and multiple regressions and redundancy analysis. Throughout the study, the presence of spatial autocorrelation was analyzed, and Spatial Eigenvector Mapping (SEVM) was used. The arid diagonal was identified as containing the smaller specimens of C. chinga, primarily related to net primary productivity (NPP). Bergmann's rule seems not to be valid for this species. Instead, evidence seems to support the "resource rule" as the primarily explanation for body size variation. A lower amount of morphological variation was explained by NPP, mainly related to relative size variation of premolar and molars.